2018
DOI: 10.1007/s00264-018-3968-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative biomechanical study on different fixation techniques in the management of transverse metaphyseal-diaphyseal junction fractures of the distal humerus in children

Abstract: From a biomechanical perspective, ESIN provides the best overall stability for fractures located in the upper region of the MDJ, while percutaneous pinning is superior in stabilizing fractures of the lower region. Two lateral and one medial pins make the most stable crossed pinning construct for these fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
2
17
0
2
Order By: Relevance
“…Pins that crossed within the MDJ region would have their centre of rotation brought closer to the fracture line, also making them less stable. Similar observation was made with cross pins in a previous biomechanical study conducted with composite bones using varying fracture heights of metaphyseal-diaphyseal fracture of the humerus [21].…”
Section: Discussionsupporting
confidence: 83%
“…Pins that crossed within the MDJ region would have their centre of rotation brought closer to the fracture line, also making them less stable. Similar observation was made with cross pins in a previous biomechanical study conducted with composite bones using varying fracture heights of metaphyseal-diaphyseal fracture of the humerus [21].…”
Section: Discussionsupporting
confidence: 83%
“…In a previous biomechanical study conducted with composite bone models [12], K-wires were found to be superior to both ESIN and EF in stabilizing transverse fractures that are located in the lower MDJ region. Other fracture patterns such as fractures with coronal obliquity were however not investigated in that study.…”
Section: Discussionmentioning
confidence: 84%
“…This reconstructed surface humerus model was then imported into SolidWorks 2016 edition (Dassautt Systemes-Simula, France) in international graphic interactive standard (IGES) format, for solid model generation and fracture and fixation simulations. Before fracture simulation, the distal MDJ region was determined as previously described [7,12]. Three different distal humerus MDJ fracture patterns including transverse, medial oblique, and lateral oblique fractures were simulated in the coronal plane.…”
Section: Fracture and Fixation Simulationsmentioning
confidence: 99%
See 2 more Smart Citations